91.5k views
4 votes
Answer number 10 no links

Answer number 10 no links-example-1
User SridharS
by
5.0k points

2 Answers

4 votes

Answer: 6

Step-by-step explanation:if you add -5 1/3 plus (-2/3) that equals to -6 and if you are adding you gotta add a positive 6 to the negative 6 and that makes 0

User Cem Ikta
by
5.2k points
1 vote

Hello There!!

Given:-


- 5 (1)/(3) + ( - ( 2)/(3) ) + ? = 0

To find

The missing term

Taking the missing term as "x"

Solution


- 5 (1)/(3) + ( - ( 2)/(3) ) + ? = 0 \\ \\ \implies - ( 16)/(3) - (2)/(3) + x = 0 \\ \\ \implies ( - 16 - 2)/(3) + x = 0 \\ \\ \implies ( - 18)/(3) + x = 0 \\ \\ \implies \cancel ( - 18)/(3) + x = 0 \\ \\ \implies - 6 + x = 0 \\ \\ \implies x = 0 + 6 \\ \\ \implies x = \red6


\therefore \tt{The \: \: missing \: \: term= 6}

Hope This Helps

User Tomzx
by
4.3k points